2014
DOI: 10.1186/1756-8722-7-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a promising PI3K inhibitor for the treatment of multiple myeloma through the structural optimization

Abstract: BackgroundWe previously reported a PI3K inhibitor S14161 which displays a promising preclinical activity against multiple myeloma (MM) and leukemia, but the chiral structure and poor solubility prevent its further application.MethodsSix S14161 analogs were designed based on the structure–activity relationship; activity of the compounds in terms of cell death and inhibition of PI3K were analyzed by flow cytometry and Western blotting, respectively; anti-myeloma activity in vivo was performed on two independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 42 publications
0
44
0
Order By: Relevance
“…Whole cell lysates were prepared for immunoblotting as described previously . Equal amounts of total proteins (30 μg) were subjected to SDS‐PAGE separation, followed by immunoblotting analysis with specific antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…Whole cell lysates were prepared for immunoblotting as described previously . Equal amounts of total proteins (30 μg) were subjected to SDS‐PAGE separation, followed by immunoblotting analysis with specific antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…There were four genes enriched in focal adhesion pathway, such as CCND2, IGF1R, LAMC1, and TLN2. Previous studies have reported that the dysregulation of PI3K‐Akt signaling pathway was closely related to MM and may be the potential therapeutic target for MM in the future . In addition, CCND2 had been reported many times in reducing apoptosis of MM cells .…”
Section: Resultsmentioning
confidence: 99%
“…PI3K / AKT signaling pathway is important for MM cell proliferation, survival and anti-apoptosis. Reduced activation of PI3K gene leads to MM cell death but increased activation of PI3K gene lead to proliferation (16). Study of Azabu and et al (17) in 2013, they detected increased expression of genes in PI3KCA.…”
Section: Discussionmentioning
confidence: 97%